Measuring the likeliness among young adults to green their homes - Toh, Tien-Choon; Goh, Kai-Chen; Goh, Hui-Hwang; Yong, Felicia Yan-Yan; Lim, Cheng-Sim; Lee, Chia Kuang (IOP Publishing, 2019)
It requires a team effort to reduce our overall impact on the planet earth. If each of us would do our parts, we could preserve the environment well and give our future generations a clean and comfortable place to live. Sustainability starts at home. Ways to green our homes have been suggested by people from all walks of life and are easily available as well. However, very little attention has been paid to the extent to which the people would take the initiative to green their homes. With the intention to explore the topic of home greening, this research aims to measure the likeliness among young adults to green their homes. Young adults are targeted because they are future leaders and their actions today will have an effect on the quality of the environment for the next fifty to one hundred years. The data needed are collected using a self-administered structured questionnaire. Eighty-eight young adults living in the Klang Valley of Malaysia have responded to the survey form but only eighty-five sets of it are analysable after detecting outliers. Mean ranking analysis is performed to rank the home greening efforts made by the respondents. The results show that the respondents have highest tendency to use energy-efficient appliances and water-saving devices, fixtures, and technologies for their homes to save the environment. On the contrary, the respondents have lowest tendency to find creative ways to recycle household goods at their homes to save the environment. In general, there is no significant difference in the home greening tendency levels of males and females.